2014
DOI: 10.1242/jeb.096743
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic scope fails to explain the detrimental effects on growth resulting from warming and elevated CO2 in Atlantic halibut

Abstract: As a consequence of increasing atmospheric CO 2 , the world's oceans are becoming warmer and more acidic. Whilst the ecological effects of these changes are poorly understood, it has been suggested that fish performance including growth will be reduced mainly as a result of limitations in oxygen transport capacity. Contrary to the predictions given by the oxygen-and capacity-limited thermal tolerance hypothesis, we show that aerobic scope and cardiac performance of Atlantic halibut (Hippoglossus hippoglossus) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
134
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 210 publications
(150 citation statements)
references
References 45 publications
14
134
2
Order By: Relevance
“…1A and fig. 3 in original article (Gräns et al, 2014)]. This clear mismatch in thermal profiles for aerobic scope and growth indicates that oxygen delivery capacity does not decrease at high temperatures and cannot have limited growth, as OCLTT would have predicted.…”
Section: Hans-otto Pörtnermentioning
confidence: 96%
See 1 more Smart Citation
“…1A and fig. 3 in original article (Gräns et al, 2014)]. This clear mismatch in thermal profiles for aerobic scope and growth indicates that oxygen delivery capacity does not decrease at high temperatures and cannot have limited growth, as OCLTT would have predicted.…”
Section: Hans-otto Pörtnermentioning
confidence: 96%
“…The resulting mobilisation of cardiac functional reserves and pattern of cardiac limitation would fit the condition of enforced fatiguing exercise more than the subtle thermal limitation seen in growth, at first caused by limited cardiocirculatory capacity and associated cost increments, and the resulting shift in energy We appreciate the on-going discussion and healthy evaluation of the hypothesis of oxygen and capacity limitation of thermal tolerance (OCLTT). However, we think it is unfortunate that Pörtner (Pörtner, 2104) sees little value in our study (Gräns et al, 2014), which currently represents the largest long-term experimental test of OCLTT. The OCLTT hypothesis emphasises the importance of oxygen delivery to aerobic processes as the major evolutionary constraint shaping organisms, their physiology and ecosystems.…”
mentioning
confidence: 97%
“…It has been contended that this loss of aerobic scope coincides with apparent decreases in tissue oxygen supplies and T HF (Farrell et al, 2009;Pörtner and Farrell, 2008;Pörtner and Peck, 2010;Wang and Overgaard, 2007). However, recent reappraisals indicate that thermal limitations on aerobic scope occur at temperatures above those constraining other crucial parameters, such as fish growth, reproduction and locomotion (Clark et al, 2013;Gräns et al, 2014;Healy and Schulte, 2012). Moreover, oxygen supply may still be adequate where these parameters fail, and potentially at and above temperatures where aerobic scope fails (Gräns et al, 2014;Iftikar and Hickey, 2013).…”
Section: The Impact Of Heat Stress On Mitochondrial Bioenergeticsmentioning
confidence: 99%
“…However, recent reappraisals indicate that thermal limitations on aerobic scope occur at temperatures above those constraining other crucial parameters, such as fish growth, reproduction and locomotion (Clark et al, 2013;Gräns et al, 2014;Healy and Schulte, 2012). Moreover, oxygen supply may still be adequate where these parameters fail, and potentially at and above temperatures where aerobic scope fails (Gräns et al, 2014;Iftikar and Hickey, 2013).…”
Section: The Impact Of Heat Stress On Mitochondrial Bioenergeticsmentioning
confidence: 99%
“…Currently, the potential synergistic effects of increased temperature and increased Ṗ CO 2 in fish have only been examined in a small number of studies (Pankhurst and Munday, 2011;Nowicki et al, 2012;Strobel et al, 2012;Enzor et al, 2013;Strobel et al, 2013a;Strobel et al, 2013b;Gräns et al, 2014). We have previously shown that increased temperature and Ṗ CO 2 levels result in a rapid increase in resting metabolic rates in several species of Antarctic fish (Enzor et al, 2013).…”
Section: Introductionmentioning
confidence: 99%